Interobserver agreement for the direct and indirect signs of pulmonary embolism evaluated using contrast enhanced magnetic angiography. (2020) - Tsuchiya, Nanae; Benson, Donald G.; Longhurst, Colin; François, Christopher J.; Reeder, Scott B.; Repplinger, Michael D.; Schiebler, Mark L.
Highlights: Direct findings of pulmonary embolism on MRA chest exms had the highest interobserver agreement for vessel cutoff (k-.52, p value-, .0001). Indirect findings for pulmonary embolism on MRA chest had the highest interobserver agreement for pleural effusions (k-.56, p value = .0001). There was high interobserver agreement for meaurement of the pulmonary artery and the right ventricle/left ventricle ratio. Abstract: Background: Accurate diagnosis of pulmonary embolism (PE) using contrast enhanced MRA (CE-MRA) requires awareness of both the direct and indirect findings of PE. Purpose: To evaluate reader agreement of the direct and indirect findings of PE on CE-MRA. Methods: We evaluated pulmonary artery diameter, right ventricle/left ventricle ratio, and clot/vessel lumen signal intensity ratio. Also, eight direct and eight indirect findings of PE were interpreted twice by two radiologists with different experience levels. The prevalence, and intra- and inter-reader agreement for the direct and indirect findings of PE were recorded. Statistical analysis of the measurements was assessed using intraclass correlation while Cohen's kappa test determined inter- and intra-reader agreement. Results: We reviewed 66 positive CE-MRA exams, 10 of which cases were used for training. The largest PE for each of the remaining 56 cases (40 woman) were included in this analysis (38.9 ± 19.7 (mean age (years) ± S.D.)). The highest interobserver agreement for the direct findings were vessel cutoff (κ = 0.52, 95 % CI = (0.30, 0.74), p < .0001) and bright clot (κ = 0.51, 95 % CI = (0.26, 0.78), p = .0001). The highest interobserver agreement for the indirect findings were for atelectasis (κ = 0.67, 95 % CI = (0.49, 0.87), p < .0001), pleural effusions (κ = 0.56, 95 % CI = (0.32, 0.79), p = 0001) and blank slate sing (κ = 0.56, 95 % CI = (0.18, 0.94), p < .0001). Conclusion: The indirect findings of atelectasis and pleural effusion had better interobserver reproducibility than the direct findings of vessel cutoff and bright clot. The intraobserver reproducibility of the direct and indirect findings is dependent on experience level. Summary statement: Using contrast enhanced magnetic resonance angiography for the diagnosis of pulmonary embolism, the indirect findings of atelectasis and pleural effusion had better interobserver reproducibility than the direct findings of vessel cutoff and bright clot.